2005
DOI: 10.1136/bjsm.2004.016402
|View full text |Cite
|
Sign up to set email alerts
|

Rugby World Cup 2003 injury surveillance project

Abstract: Objectives: To study match injury patterns and incidence during the Rugby World Cup 2003 (RWC 2003); to compare these patterns and rates with comparative rugby injury data; and to assess differences between teams playing at different levels (eight finalists v 12 non-finalists). Methods: Data were collected prospectively during the tournament. All injuries were recorded by the 20 participating team physicians. These were submitted to the tournament medical officer. An injury was defined as an event which forced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
73
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 6 publications
10
73
2
Order By: Relevance
“…It ranked sixth after soccer (13.9%), basketball (13.4%), volleyball (7.1%), long-distance running (6.3%) and cycling (6.3%). Jorgensen and Winge (1987) reported that the incidence rate was 2.9 per 1,000 player-hours, which was much lower than those injury incidence rates for contact sports such as soccer (Junge and Dvorak 2004), rugby (Best et al 2005) and 4 basketball (McKay et al 2001) that often exceeded 10.0 per 1,000 player-hours.…”
Section: Introductionmentioning
confidence: 95%
“…It ranked sixth after soccer (13.9%), basketball (13.4%), volleyball (7.1%), long-distance running (6.3%) and cycling (6.3%). Jorgensen and Winge (1987) reported that the incidence rate was 2.9 per 1,000 player-hours, which was much lower than those injury incidence rates for contact sports such as soccer (Junge and Dvorak 2004), rugby (Best et al 2005) and 4 basketball (McKay et al 2001) that often exceeded 10.0 per 1,000 player-hours.…”
Section: Introductionmentioning
confidence: 95%
“…Front row forwards encounter high levels of static exertion where the intensity rather than the quantity of scrummaging has been suggested to cause transient neuromuscular fatigue [19], which is likely to reduce subsequent performance and may be a predisposing factor for injury [1]. To date, research has focused on determining scrum force of front row forwards and its impact on engagement technique and injury occurrence [9,16], but there is a paucity of research investigating the effect of possible fatigue from repetitive scrummaging.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, the injury incidence in Rugby World Cup matches was 83.9-97.9 injuries/1000 player hours (ph) [1][2][3] . While knee injuries had the highest mean severity of all match injuries, knee ligament injuries were responsible for the greatest time loss 3) ; therefore, prevention of knee injuries in rugby is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies [1][2][3]5,6) have indicated the incidence of knee injuries in rugby union players, many surveys have been limited to the professional level. In general, the incidence rate of knee ligament injury is high in young people, and many cases have required surgical intervention.…”
Section: Introductionmentioning
confidence: 99%